An improved 220‐GHz RF CMOS compact equivalent circuit model considering magnetic coupling effect. Issue 4 (13th November 2020) - Liu, Xusheng; Liu, Jun; Yu, Yiming; Zhao, Chenxi; Liu, Huihua
Abstract: In this study, an improved RF CMOS transistor compact equivalent circuit model is presented. Due to the finite resistivity of the substrate, the magnetic coupling effect between the interconnection line and the substrate affects the signal propagation at mm‐wave frequency range. To characterize transistors in the terahertz band, a sophisticated network is introduced to represent the magnetic field of interconnection lines and substrate image current. In addition, the parameters of the proposed model are extracted by an analytical method. By comparison with the reported model, the proposed model can significantly improve the phase accuracy. The comparison of calculation results and experimental data shows that the proposed model can well characterize the transistor up to 220 GHz.